Museums, Climate Change and Energy Education: A Digital Discourse Analysis - Francesca Patten; Gregory Lowan-Trudeau (Australian Journal of Environmental Education)
The purpose of this study was to explore how science and environmentally related museums in Alberta, Canada are digitally engaging with climate change and energy education. This inquiry utilised qualitative discourse analysis to examine the discourses, dynamics and tensions present in digital museum contexts related to climate and energy education in Alberta. Drawing on Eisner’s three curricula — the explicit, implicit and null — the study focused on museums’ websites and social media activity. The museums studied share common foci on science, environment, or energy but range in size and location. As a long-standing energy-based economy, Alberta provides an interesting, and often contested, setting to observe climate and energy education in practice at museums, many of which exist in communities and within governance and stakeholder networks which are connected to the energy industry. Discourse-connected findings, discussion and implications are presented in relation to museums’ institutional mandates, curricular initiatives, pedagogical practices, special events and infrastructure initiatives.